Impact of drainage on yield of Musa Sapientum - Baidoo-Antwi, Enock Innocent (University of Mines and Technology, 2019)
This report sought to confirm that drainage has impact on the number of flowers counted on Musa Sapietum Plantation in GEL. Beginning with the advantageous location of the plantation for three major reasons, of relative closeness to the Sea port, abundance of water for irrigation and weather condition not favourable for bleeding harmful insects. The objectives of this thesis are to find out if drain depth has influence on yield and Secondly to what extent should drain depth be essential for banana cultivation. Water for Irrigation was supplied to the plants as it is required but due to high permeability of the soil or rainfall, drainage were constructed to aid in removing excess water from around the roots in the soil. Sector 1 through to Sector 4 of Golden Exotics Ltd (GEL) plantation was used as a case study. The methods used were taking field drain measurements to determine the average drain depth per plot in each Sector. And collection of production data for Year 2017 which was used to calculate the average number of bunches harvested per plot. Microsoft Excel 2013 from GEL was then used to analyse the data to establish the findings of this project which concludes that the average number of bunches increased from depth range of 0.0 m - 0.3 m to 0.31 m – 0.6 m but there was no significant increase from drain depth from 0.9 m and above. ANOVA a statistical F test tool was used to test the significance of each depth range and average number of bunches harvested at 5% Significance.
xi, 69p; ill.
Keywords: Impact of drainage; Environmental issues; Agriculture; Geoscience; Soil science